Peatland Microbial Communities and Decomposition Processes in the James Bay Lowlands, Canada - Preston, Michael D.; Smemo, Kurt A.; McLaughlin, James W.; Basiliko, Nathan (Frontiers in Microbiology, 2012)
Northern peatlands are a large repository of atmospheric carbon (C) due to an imbalance between primary production by plants and microbial decomposition. The James Bay Lowlands (JBL) of northern Ontario are a large peatland complex but remain largely unstudied. Climate change models predict the region will experience warmer and drier conditions, potentially altering plant community composition and shifting the region from a long-term carbon sink to a source. We collected a peat core from two geographically separated (ca. 200 km) ombrotrophic peatlands (Victor and Kinoje Bogs) and one minerotrophic peatland (Victor Fen) located near Victor Bog within the JBL. We characterized (i) archaeal, bacterial and fungal community structure with terminal restriction fragment length polymorphism of ribosomal DNA, (ii) estimated microbial activity using community level physiological profiling and extracellular enzymes activities, and (iii) temperature dependence of C mineralization at three depths (0-10, 50-60 and 100-110 cm) from each site. Similar dominant microbial taxa were observed at all three peatlands despite differences in nutrient content and organic matter quality. In contrast, we observed differences in basal respiration, enzyme activity and the magnitude of substrate utilization, which were all generally higher at Victor Fen and similar between the two bogs. However, there was no preferential mineralization of C substrates between the bogs and fens. Microbial community composition did not correlate with measures of microbial activity but pH was a strong predictor of activity across all sites and depths. Increased peat temperature and aeration stimulated CO2 production but this did not correlate with a change in enzyme activities. Potential microbial activity in the JBL appears to be influenced by the quality of the peat substrate and the presence of microbial inhibitors, which suggests the existing peat substrate will have a large influence on future JBL C dynamics.